Application of Calixarenes as Macrocyclic Ligands for Uranium(VI): A Review - Katarzyna Kiegiel; Lukasz Steczek; Grazyna Zakrzewska-Trznadel (Journal of Chemistry)
Calixarenes represent a well-known family of macrocyclic molecules with broad range of potential applications in chemical, analytical, and engineering materials fields. This paper covers the use of calixarenes as complexing agents for uranium(VI). The high effectiveness of calix[6]arenes in comparison to other calixarenes in uranium(VI) separation process is also presented. Processes such as liquid-liquid extraction (LLE), liquid membrane (LM) separation, and ion exchange are considered as potential fields for application of calixarenes as useful agents for binding UO22+ for effective separation from aqueous solutions containing other metal components.